Cleaning and Surface Treatment Protocols for Repair of Aged Y-TZP with Composite Resin - Barchetta, Nayara Fernanda [UNESP]; Silva, Ana Carolina [UNESP]; Domingues, Nadia [UNESP]; Braga Pereira, Sarina Maciel [UNESP]; Bottino, Marco Antonio [UNESP]; Ferreira Anzaloni Saavedra, Guilherme de Siqueira [UNESP]; Melo, Renata Marques de [UNESP]; Assuncao e Souza, Rodrigo Othavio de (Quintessence Publishing Co Inc, 2021)
The purpose of this study was to evaluate the cleaning and surface treatment techniques in the repair of aged and contaminated yttrium oxide-stabilized tetragonal polycrystalline zirconia (Y-TZP). From a total of 80 specimens of Y-JZP, 60 were subjected to aging simulation in a buccal environment with degradation in an autodave for 24 hours (127 degrees C/1.5 bar) and contaminated with Streptococcus mutans. The surfaces were cleaned with a triple syringe (air/water jet; n = 20) or isopropyl alcohol (n = 20), or by prophylaxis (n = 20) with pumice and water. The remaining 20 specimens comprised the control group. All specimens were then treated with silicatization (n = 10 per group) or adhesive (n = 10 per group) and repaired with composite resin. Analyses of shear strength, failure mode, and roughness were performed by electron microscopy. Data were analyzed by two-way analysis of variance (ANOVA) and t test (alpha = .05). Statistical significance was set at P < .05. Two-way ANOVA was significant for aging and surface treatments (P = .049), but was not significant for surface cleaning (P = .05). ANOVA results were statistically significant for surface treatments (P < .0001), with higher resistance for the silicatization groups. The failure mode was mostly adhesive for all specimens. The roughness was not significant for aging and control groups (P > .05). Triple-syringe and prophylaxis cleansing followed by silicatization was the most efficient treatment for the repair of aged and contaminated Y-TZP. There is reduced repair efficiency with the aging of Y-TZP.